The effect of comboplough on some soil physical properties of Universiti Putra Malaysia Research Park - Hashemi, A.; Ahmad, Desa; Othman, Jamarei; Sulaiman, Shamsuddin (Academic Journals, 2014)
A disk plough combined with a set of rotary blades (comboplough) for land preparation has been designed, fabricated and tested. The concave disk cut and inverted layers of soil to bury surface material. The soil in contact with the surface of disk would be cut and pulverized by the rotary blades. Normal multiple tillage operations were reduced to a single pass and thus reduced the number of field trips as compared to conventional tillage practices resulting in a potential reduction of soil compaction, labor, fuel cost and time. The comboplough was tested in the Serdang sandy clay loam soil texture at Universiti Putra Malaysia Research Park. The treatments consisted of three types of blade (straight type or S blade, C-shaped and L-shaped) and three rotary speeds (130, 147 and 165 rpm). Mean Weight Diameter Dry basis (MWDd), mean weight diameter wet basis (MWDw), stability index (SI), instability index (II), 2 to 8 mm aggregate size distribution (ASDd8) and 0 to 100 mm aggregate size distribution (ASDd100) were determined and analyzed. The results indicated that no significant differences were noted between types of blade. However, the rotational speeds had significant effects on selected parameters.